ASSESSMENT OF THE RISK TO THE HEALTH OF THE POPULATION OF AN INDUSTRIAL CENTER DUE TO THE EXPOSURE OF ATMOSPHERIC EMISSIONS OF THE PETROLEUM DEPOT - Вера Викторовна Кислицына; Дмитрий Вячеславович Суржиков; Юлия Сергеевна Ликонцева; Варвара Адамовна Штайгер (Медицина в Кузбассе, 2023)
The aim of the research was the assessment of the risk to the health of the population of an industrial center due to the air pollution by the emissions from a petroleum depot.